2008
DOI: 10.1093/treephys/28.4.615
|View full text |Cite
|
Sign up to set email alerts
|

Water use and carbon exchange of red oak- and eastern hemlock-dominated forests in the northeastern USA: implications for ecosystem-level effects of hemlock woolly adelgid

Abstract: Water use and carbon exchange of a red oak-dominated (Quercus rubra L.) forest and an eastern hemlock-dominated (Tsuga canadensis L.) forest, each located within the Harvard Forest in north-central Massachusetts, were measured for 2 years by the eddy flux method. Water use by the red oak forest reached 4 mm day(-1), compared to a maximum of 2 mm day(-1) by the eastern hemlock forest. Maximal carbon (C) uptake rate was also higher in the red oak forest than in the eastern hemlock forest (about 25 versus 15 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…Gaps in HEM data were filled using non-linear regression (Hadley et al 2008). For those times when neither partitioned nor gap-filled NEE data (Barr et al 2004, Amiro et al 2006 to estimate R e because it gave good agreement with available gap-filled values from HEM (Appendix: Fig.…”
Section: Ecosystem-scale Co 2 Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaps in HEM data were filled using non-linear regression (Hadley et al 2008). For those times when neither partitioned nor gap-filled NEE data (Barr et al 2004, Amiro et al 2006 to estimate R e because it gave good agreement with available gap-filled values from HEM (Appendix: Fig.…”
Section: Ecosystem-scale Co 2 Measurementsmentioning
confidence: 99%
“…The longest time series of soil temperature at 10-cm depth in a forested area was collected at the Little Prospect Hill (LPH) eddy-covariance site, with half-hourly data available from 2002 to 2009 (herein T s10,LPH ; Hadley et al 2008). Red oak is the dominant tree species at the LPH site; this is the same species that dominates the EMS tower footprint, although the LPH stand is younger.…”
Section: Estimation Of R S At Eddy-covariance Sitesmentioning
confidence: 99%
“…Th is contrasts with studies that predicted signifi cant changes in water use due to the loss of hemlock canopies and a resulting change in soil water content. For example, Hadley et al (2008) measured water use in red oak (Quercus rubra L.) and hemlock forests in the U.S. Northeast and their data suggested that following an initial increase in soil water content due to reduced evapotranspiration, replacement of hemlock by hardwood species would probably decrease the summertime soil water content due to increased water use by hardwoods. used a combination of sap fl ow measurements and modeling to predict the impacts of HWA on transpiration and predicted a 30% decrease in total transpiration during the winter and spring following complete loss of hemlock.…”
Section: ) -------------P Input G P Ha −1 -------------mentioning
confidence: 99%
“…Although hemlock defoliation was occurring rapidly, the dense R. maximum evergreen understory maintained shaded conditions, which may have prevented changes in the soil temperature with time. For soil water content, increased water uptake by hardwood species (Hadley et al, 2008) may have off set decreased water uptake by hemlock. Additionally, predicted transpiration declines in winter and spring only, a time when soils are near fi eld capacity due to limited water use by hardwoods.…”
Section: ) -------------P Input G P Ha −1 -------------mentioning
confidence: 99%
“…In the mosaic of eastern forests, stands of hemlock provide stark contrast to the matrix of deciduous and pine forests. In riparian areas, where they often dominate, hemlocks moderate stream flow and diurnal temperature fluxes (Ellison et al 2005, Hadley et al 2008.…”
Section: Introductionmentioning
confidence: 99%